The impact of economic growth, energy consumption and trade openness on carbon emissions: An empirical analysis in China - Jianxu Liu (2019)
© Springer Nature Switzerland AG 2019. The study aims to test the long-run cointegration relationship and causality among China’s carbon emissions, economic growth, energy consumption and trade openness for the period 1971–2013. Autoregressive Distributed Lag (ARDL) model incorporating with structural breaks and Vector Error Correction Model (VECM) Granger causality test are applied in this study. The empirical results reveal that inverted-U shape relationship exists between carbon emissions and economic growth in the long-run, but it doesn’t hold in short-run, proving that Environmental Kuznets Curve (EKC) is a long-run phenomenon rather than short-run. Moreover, energy consumption and trade openness are found to have positive impacts on carbon emissions in the long-run and short-run. As for causality test the result showed that bi-directional causal relationship exists between energy consumption and carbon emissions in the long-run. In the short-run, unidirectional causality is found running from trade openness to carbon emissions.